2018
DOI: 10.1177/1356336x18797363
|View full text |Cite
|
Sign up to set email alerts
|

Hybridizing pedagogical models: A systematic review

Abstract: The goal of this study was to assess hybridizations conducted among pedagogical models (PMs) from 1st to 12th grade (six–18 years) in physical education (PE). Research articles selected were found through Web of Science, Medline, Scopus, SportDiscus (EBSCO), ERIC (ProQuest) and Google Scholar databases. The keywords associated with PMs (e.g. models-based practice and sport education (SE)), hybridization (e.g. hybrid), PE and educational levels (e.g. middle school) were used in different combinations. The artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(124 citation statements)
references
References 64 publications
6
100
0
18
Order By: Relevance
“…We therefore do not agree with the study by García et al (2014), where the teaching staff indicate that the innovative methodologies for promoting autonomy and responsibility are perceived as complex to apply due to the limited time available, given that there was only one comment that indicated "the day I get confused I don't get to the evaluation, or I set the alarm on my mobile phone 5 min before the end of the class". Furthermore, the possibility of hybridizing with other pedagogical models such as Cooperative Learning, could improve some of the potential or educational results that TPSR has in a unique way (González-Víllora et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore do not agree with the study by García et al (2014), where the teaching staff indicate that the innovative methodologies for promoting autonomy and responsibility are perceived as complex to apply due to the limited time available, given that there was only one comment that indicated "the day I get confused I don't get to the evaluation, or I set the alarm on my mobile phone 5 min before the end of the class". Furthermore, the possibility of hybridizing with other pedagogical models such as Cooperative Learning, could improve some of the potential or educational results that TPSR has in a unique way (González-Víllora et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(Higgins et al, 2016) adapting several items by the Strengthening the Reporting of Observation Studies statements (von-Elm et al, 2008). Additionally, in order to obtain an overall quality score for each study, an exhaustive analysis were carried out based on the systematic review procedure showed in González-Víllora et al (2018). Finally, the quality of the systematic review and meta-analysis was evaluated using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA; Moher et al, 2009).…”
Section: Search Process Data Extraction and Use Of Softwarementioning
confidence: 99%
“…Hybridizations of MsBP might be the solution to extend the benefits of implementing single MsBP (González-Víllora et al, 2018). However, it is also supported the idea of combining single MsBP or parts of them.…”
Section: Implementation Of Hybridizations and Its Impact On The Studementioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Pujolás [20] and Muñiz et al [21] state that learning based on the cooperative structure can be a useful tool for all ages and contexts and for students with both low and high performance. Research based on cognitive styles has shown that there are different ways of learning and approaching knowledge, which profoundly affect the performance of individuals and their approach to education for sustainable development [22].…”
Section: Introductionmentioning
confidence: 99%